KELAYAKAN FINANSIAL USAHA PERIKANAN TANGKAP DI SELAT BALI - Syafril Fauzi; Budhi Hascaryo Iskandar; Bambang Murdiyanto; Eko Sri Wiyono (Fakultas Perikanan dan Ilmu Kelautan, 2011)
Fishing effort become the dominant (about 80%) of the fishing economy and society in the Bali Strait. This situation quiet long when fishing effort is not well managed and there is no balance in financial terms. This study will assess the condition of investment, operational, and financial feasibility of the fishing effort. The method used consisted of investment analysis, NPV, IRR, ROI and BCR. The analysis showed that investment needs purse seine OBS, purse seine TBS, gill nets and payang is 287,750.000, Rp 476.25 million, Rp 313,250,000 and Rp 261,150,000. The annual operational needs OBS purse seine, purse seine TBS, gill nets and successive payang is 261,965,000, USD 408.87 million, Rp 234,550,000 and Rp 188,717,500. While the annual revenue purse seine OBS, purse seine TBS, gill nets and payang is Rp 992,928,000, Rp 1,998,132,000, Rp 673,292,000 and Rp 636,290,000. These four fishing gear are 'very feasible' developed in Bali strait, because it has the value of NPV, IRR, ROI, and B/C ratio is better than required. Purse seine OBS have Rp 1,755,080,046.41 NPV, IRR of approximately 102.55%, ROI around 21.22, and R/C ratio of about 1.40. Purse seine TBS has NPV around Rp 4,070,067,018.54, IRR around 140.15%, ROI around 25.80, and R/C ratio about 1.50. Gill net has a NPV about Rp 918,548,267.25, IRR about 53.08%, ROI around 13.66, and R/C ratio about 1.27, and payang have NPV around Rp 982,670,737.88, IRR of approximately 66,25%, ROI around 14.98, and R/C ratio about 1.34.